The efficacy of interprofessional simulation in improving collaborative attitude between nursing students and residents in medicine. A study protocol for a randomised controlled trial - Ferri, Paola; Rovesti, Sergio; Magnani, Daniela; Barbieri, Alberto; Bargellini, Annalisa; Mongelli, Francesca; Bonetti, Loris; Vestri, Annarita; Alunni Fegatelli, Danilo; Di Lorenzo, Rosaria (Acta Biomedica Atenei Parmensis, 2018)
Background: Effective collaboration among health professionals is an essential component to ensure quality of care. Many adverse events experienced by patients are attributed to misunderstanding or poor communication among members of the interprofessional team. Interprofessional simulation is a learning strategy used to improve collaboration and facilitate communication between medical and nursing students. Aim of the work: To determine the efficacy of educational program based on high-fidelity interprofessional simulation aimed at improving collaborative attitude. Method: For this purpose, a protocol for a planned single-center, non-blinded and Randomized Controlled Trial (RCT) was chosen. The present has been approved by the Ethics Committee of Area Vasta Emilia Nord (Italy) (n° 479/2018). All students attending the second and third year of nursing and all resident physicians in anesthesia, reanimation, intensive care and pain management of University of Modena and Reggio Emilia, will be recruited and randomly assigned to two groups. The Experimental Group (EG) will receive an educational intervention based on high-fidelity simulation and the Control Group (CG) will attend a traditional classroom lesson. Jefferson Scale of Attitudes toward Physician-Nurse Collaboration (JSAPNC) and Readiness for Interprofessional Learning Scale (RIPLS) will be administered before and after the educational program in both the EG and CG. Conclusion: Expected outcomes is that, at the end of the study, nursing students and resident physicians who participated in the interprofessional simulation show significantly higher levels of interprofessional collaboration compared to the CG, evaluated through the JSAPNC.